Diseño de un programa interactivo para tratar la sexualidad sin mitos y evitar embarazos no deseados, dirigido a los estudiantes y padres de familia de 8° y 9° a.e.g.b. del colegio “Gonzalo Albán Rumazo” del cantón Latacunga, durante el año lectivo 2012-2013 - Chillagana Ramírez, Darwin David (2013)
Education for sexuality is one of the objectives of the educational work and it is for the student’s preparation related with a responsible and full encounter with it´s sexuality, in correspondence of with its necessities and those of its context. With the purpose of solving the lack of preparation, families and teachers, is have to orient adolescents towards sexuality, and particularly, in the assumption of psychosexual change that opperate in their personalities with an integral vision. Therefore, the authors of this work propose a system in order to develop of the actions favor sexual education in the adolescent. This work has an extraordinary importance nowadays to prevent flashy behaviors together with, some of other aspects of interest regarding teenagers such as: the decrease of early sexual relations as well as, early maternity, which all of them, and usually the main cause of school desertion.